PENGARUH PENYULUHAN PAJAK, SURAT PEMBERITAHUAN PAJAK TERUTANG (SPPT), SANKSI PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN PAJAK BUMI DAN BANGUNAN DI MASA PANDEMI: Indonesia - Lina Putri Selina; Dita Anggi Mawarni; Mega Yulianti; Yuli Maelani (Journal of Taxation Analysis and Review, 2021)
Taxpayer Compliance is a condition in which the taxpayer fulfills his tax rights and obligations. The purpose of this study was to determine the effect of counseling, SPPT, tax sanctions, and public awareness of land and building taxpayers in Subang Regency. The population in this study were 1,506,293, with a sample size of 100 respondents using the Slovin formula. The data in this study were collected through a questionnaire. The tests used were validity tests, reliability tests, classical assumptions and multiple linear regression analysis. Simultaneously, tax counseling variables and public awareness have a positive effect on land and building taxpayer compliance, while partially tax returns and tax sanctions have a significant negative effect on land and building taxpayer compliance. .